(untitled) (Journal of Hama University, 2024)
The research studied the chemical work system in AL-Qusayr plant, which includes sterilization and coagulation. Recently, the sterilization system was modified by replacing chlorine gas with calcium hypochlorite, which contains an active substance of 70%. Despite the advantages of gas sterilization, it was replaced by hypochlorite compounds due to the lack of cylinders, and work was done on new equipment for supplying powder, and studying the most important differences between the two methods. The coagulant (Aqueous Aluminum Sulfate) was added at the perfect dose 3 mg/l with the following indicators installed: pH = (5.5-7.5), coagulation time = (20-60) sec, flocculation time = 35 min. It was found that if the alum solution was not stirred in the tank during its consumption, or the stirring process took place at long intervals, the added dose would become incorrect, the dosing pumps would become clogged, and a loss in the coagulant would occur. Therefore, the research recommended the following points to obtain water with better specification: 1- The alum tank mixer must be operated every two hours for half an hour, so that the dosing pumps work more stable. 2- The discharge of the coagulant dosing pump should be stabilized by installing a Hertz converter with a value of (19.5 – 24.5) Hz within 24 hour, to control the amount of Aqueous Aluminum Sulfate solution dosed momentarily, so that the level of the solution decreases by 10 cm/h and the discharge is equivalent to 975 l/h. This was reflected positively on the efficiency of the work of station, this was shown by reducing the consumption of alum and the energy used in the filter washing operations and increasing the investment life of the mechanical and electrical equipment used in the process of preparing the alum solution and washing the filters.